2005
DOI: 10.1021/bi050356t
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Induced Tryptophan Fluorescence Changes in EmrE, the Smallest Ion-Coupled Multidrug Transporter

Abstract: Tryptophan residues may play several roles in integral membrane proteins including direct interaction with substrates. In this work we studied the contribution of tryptophan residues to substrate binding in EmrE, a small multidrug transporter of Escherichia coli that extrudes various positively charged drugs across the plasma membrane in exchange with protons. Each of the four tryptophan residues was replaced by site-directed mutagenesis. The only single substitutions that affected the protein's activity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
64
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 39 publications
7
64
0
Order By: Relevance
“…Purification was performed essentially as in Ref. 7. Reconstitution was performed as described (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purification was performed essentially as in Ref. 7. Reconstitution was performed as described (28).…”
Section: Methodsmentioning
confidence: 99%
“…Trp-63 has been shown to be essential and even a conservative replacement by an aromatic residue yielded an inactive transporter (7). Tyr-40 and Tyr-60 can be only replaced with hydroxyamino acids (8).…”
mentioning
confidence: 99%
“…Trp63 is completely conserved in the SMR family, and we previously showed that it is essential for EmrE function (7). However, because we did not previously use a Gly replacement, we investigated the W63G mutant.…”
Section: Mutation At Position 63 Inactivates the Previously Known Funmentioning
confidence: 99%
“…The new mutant gained a new specificity but also conserved its ability to transport most of the original substrates. On the other hand, the mutation conferring resistance to erythromycin was a replacement of Trp63, a fully conserved and essential amino acid (7). Interestingly, this mutant completely lost the capacity to recognize and remove the classical substrates of EmrE but gained, in addition to its ability to confer resistance to erythromycin, a completely new functionthe ability to import polyamines into the cell.…”
mentioning
confidence: 99%
“…However, functionally important Trp residues are found in the binding sites of different transport proteins where they are involved in stacking or -interactions (23)(24)(25)(26)(27)(28)(29). Soluble sugar-binding proteins (30)(31)(32), as well as two sugar transport proteins, contain Trp (8) or Tyr (33) residues that undergo aromatic interactions with sugar in the binding site.…”
mentioning
confidence: 99%